2015
DOI: 10.3389/fimmu.2015.00015
|View full text |Cite
|
Sign up to set email alerts
|

Five Layers of Receptor Signaling in γδ T-Cell Differentiation and Activation

Abstract: The contributions of γδ T-cells to immunity to infection or tumors critically depend on their activation and differentiation into effectors capable of secreting cytokines and killing infected or transformed cells. These processes are molecularly controlled by surface receptors that capture key extracellular cues and convey downstream intracellular signals that regulate γδ T-cell physiology. The understanding of how environmental signals are integrated by γδ T-cells is critical for their manipulation in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 125 publications
(119 reference statements)
3
97
1
Order By: Relevance
“…Since the discovery of γδ T cells in the mid-1980s in humans, these cells have been considered as an enigmatic population that exhibits the characteristics of both innate and adaptive immune functions, such as participating in rapid resistance to pathogen infections, acting as an APC to initiate adaptive immunity, and performing CD4 + Th and CD8 + CTL-like functions (4, 30). Thus, the γδ T cells are thought to be a more primordial lymphocyte subset with a long evolutionary history throughout vertebrate evolution (31).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of γδ T cells in the mid-1980s in humans, these cells have been considered as an enigmatic population that exhibits the characteristics of both innate and adaptive immune functions, such as participating in rapid resistance to pathogen infections, acting as an APC to initiate adaptive immunity, and performing CD4 + Th and CD8 + CTL-like functions (4, 30). Thus, the γδ T cells are thought to be a more primordial lymphocyte subset with a long evolutionary history throughout vertebrate evolution (31).…”
Section: Discussionmentioning
confidence: 99%
“…γδT cells can rapidly respond to a variety of protein‐ and non‐protein‐based antigens. γδT cells express pattern recognition receptors (PRRs), including Toll‐like receptors (TLRs) and C‐type lectin receptors . Equipped with these sensors that can recognize DAMPs and pathogen‐associated molecular patterns, the role of γδT cells in inflammatory responses has been increasingly appreciated.…”
mentioning
confidence: 99%
“…Cytokines and chemokines are soluble factors that are secreted by cells to communicate among themselves, contributing to downstream effects such as activation, proliferation and recruitment, which are essential to resolving an infection. Studies have shown that γδ T cell subsets are able to respond to IL-12, IL-15, IL-18 which then leads to activation, the secretion of cytokines and proliferation [139]. In aging studies on αβ T cells, the authors have shown that elderly T cells display attenuated tyrosine phosphorylation of the protein tyrosine kinase ZAP-70, LAT and PLCγ due to TNFα and reduced phosphorylation of STAT3 and STAT5; this is possibly due to the increased expression of suppressor of cytokine signaling 3 (SOCS3) caused by IL-6.…”
Section: Cytokines Chemokines and γδ T Cellsmentioning
confidence: 99%